Glitter-like iridescence within the bacteroidetes especially Cellulophaga spp.: optical properties and correlation with gliding motility. - Betty Kientz; Adrien Ducret; Stephen Luke; Peter Vukusic; Tâm Mignot; Eric Rosenfeld (PLoS ONE)
Iridescence results from structures that generate color. Iridescence of bacterial colonies has recently been described and illustrated. The glitter-like iridescence class, created especially for a few strains of Cellulophaga lytica, exhibits an intense iridescence under direct illumination. Such color appearance effects were previously associated with other bacteria from the Bacteroidetes phylum, but without clear elucidation and illustration. To this end, we compared various bacterial strains to which the iridescent trait was attributed. All Cellulophaga species and additional Bacteroidetes strains from marine and terrestrial environments were investigated. A selection of bacteria, mostly marine in origin, were found to be iridescent. Although a common pattern of reflected wavelengths was recorded for the species investigated, optical spectroscopy and physical measurements revealed a range of different glitter-like iridescence intensity and color profiles. Importantly, gliding motility was found to be a common feature of all iridescent colonies. Dynamic analyses of "glitter" formation at the edges of C. lytica colonies showed that iridescence was correlated with layer superposition. Both gliding motility, and unknown cell-to-cell communication processes, may be required for the establishment, in time and space, of the necessary periodic structures responsible for the iridescent appearance of Bacteroidetes.